Influence of cultivation conditions and age of the culture on the production of cytostatic secondary metabolite 2505 and its natural analogues - Gajarská, Zuzana (Jihočeská univerzita, 2017)
The aim of this thesis was to investigate the effect of different cultivation conditions and age of the culture on the production of cytostatic secondary metabolite 2505 and its natural analogues in terrestrial cyanobacterium Desmonostoc sp.
Influence of cultivation conditions and age of the culture on the production of cytostatic secondary metabolite 2505 and its natural analogues
Keywords: cyanobacteria; secondary metabolites; Desmonostoc muscorum; cultivation conditions; cyanobacteria; secondary metabolites; Desmonostoc muscorum; cultivation conditions